Guinea-Bissau : Ex Post Assessment of Performance Under Fund-Supported Programs, 1993-2003. (IMF Staff Country Reports; Country Report, 2005)
This paper reviews Ex-Post Assessment of Performance Under IMF-Supported Programs for Guinea-Bissau. More than two-thirds of the population of approximately 1.3 million is living below the poverty line in Guinea-Bissau. The paper describes developments under IMF-supported programs since 1993, when Guinea-Bissau embarked on a second round of stabilization and reform efforts. It summarizes the lessons learned and the challenges for the near future. Possible future role of IMF in Guinea-Bissau is also discussed.